The concept of Tianyuan Difang and the evolution of single-sheet Tianxia Tu in ancient China (before around 1600 AD) - Yingyan Gong (International Journal of Anthropology and Ethnology)
Abstract “Tianxia Tu,” the map of all under heaven, is a type of map created by ancient Chinese based on the cosmological concept of Tianyuan Difang (the round-shaped heaven and the square-shaped earth) in ancient China. These maps exist in two primary forms: single-sheet maps and book illustrations. Single-sheet Tianxia Tu appeared as early as the Han Dynasty, while book illustrations emerged during the Northern Song Dynasty. The evolutionary genealogy of single-sheet Tianxia Tu before around 1600 AD is as follows: during the Han and Tang dynasties, these maps were painted on silk by high-ranking officials; during the Song Dynasty, they were engraved on stone steles installed in government schools to serve the imperial civil service examination (Keju Kaoshi). Around 1550, woodblock-printed Scenic and Cultural Maps of All Under Heaven emerged as popular reading materials for the general public, created by grassroots intellectuals and disseminated through market networks. Ancient Chinese cartography developed its distinct characteristics in parallel with, rather than imitating, European models. It is worth contemplating how to incorporate its positive elements while adhering to scientific principles.